Implementation of Knowledge Management Tools in Libraries: A Systematic Literature Review - Azzahrawaani, Zhafirah; Latifa Mayda Ikrimah, Awalia (Indonesian Journal of Librarianship, 2024)
Background: The lack of references for practical examples of Knowledge Management (KM) tool applications in libraries can be one of the obstacles to the development of KM tools in non-profit institutions. Therefore, conducting studies is essential to enrich and advance scientific knowledge related to library science and Knowledge Management. Purpose: The study aims to describe KM tools commonly used in both profit and non-profit organizations and review their usage in libraries. Method: This study is a systematic literature review following the PRISMA framework. A total of 31 articles were collected and subsequently analyzed based on their relevance to the research topic. Result: The use of KM tools in organizations is becoming increasingly diverse, incorporating both IT and non-IT approaches. Common types of KM tools used in organizations include social media, websites, the internet, networks, face-to-face interactions, mentoring, and reports. The concept of KM tool usage includes: (1) knowledge strategy, for developing competencies needed in the future; (2) knowledge creation, for problem-solving; (3) knowledge retention, for sharing tacit knowledge; and (4) knowledge measurement, for addressing knowledge deficiency issues. KM tools have also been adapted in libraries for managing knowledge sources and representation, storage, knowledge dissemination, and as tools for problem-solving. KM tools in libraries include the Online Public Access Catalog (OPAC), repositories, social media, face-to-face interactions, and the 'Ask the Librarian' feature. Conclusion: The use of KM tools in organizations can be adjusted to meet specific needs and budgets. Libraries, in storing information, have utilized various forms of KM tools, allowing them to effectively and efficiently fulfill their role in managing the knowledge produced by the host institutions.